Assessing Peri-Urbanisation and Urban Transitions between 2010 and 2020 in Ho Chi Minh City using an Urban Structure Type Approach - Nigel K. Downes; Harry Storch; Pham Quoc Viet; Nguyen Kieu Diem; Le Canh Dinh (Urban Science, 2024)
This paper contributes to the understanding of the recent urban development of Ho Chi Minh City, Vietnam. Previous studies have aimed at quantifying the city’s spatial growth yet have disregarded its inherent morphological and socio-economic heterogeneity. To overcome this knowledge gap, we employ an urban structure type approach for the spatially explicit quantification of urbanisation patterns for the period 2010–⁠2020, categorising 77,000 blocks across the entire administrative area of 2095 km2. The approach allows us to understand the basic underlying processes of urbanisation, both quantitatively and qualitatively, and the main growth corridors along the rural–urban gradient. By contextualizing and combining our findings within current literature and official planning reports, we discern between traditional urban growth and the contemporary new town development patterns, highlighting their driving forces and policy implications. Incremental plot-by-plot development along the northwest development corridor is observed as the principal mode of urban development, whilst bypass urbanisation is seen along both the eastern and southern development corridors. Our block-based results highlight the city’s key growth challenges and provide insights on a scale that is meaningful for official spatial and infrastructure planning, and periodic analysis and monitoring. As far as the authors are aware, this is the first time that an urban structure type approach was applied to understand the rapid urban growth dynamics of an emerging megacity in Southeast Asia.